Medical Law : A Very Short Introduction - Foster, Charles, 1962- (Oxford, New York Oxford University Press, 2013)
Everyone has an opinion about the core issues of medical law; from clinical negligence and organ transplantation to abortion, confidentiality, and euthanasia - it deals with matters of life and death. Using case studies to explore the key principles, Charles Foster presents a fascinating Very Short Introduction to medical law.
Include Index and Illustration
Keywords: Medical laws and legislation -- Patients--Legal status, laws, etc -- Great Britain